Hubungan antara Terpaan Konten “Kemis Nyunda” pada Akun Instagram @humas_bandung dengan Peningkatan Pelestarian Bahasa Sunda - Fadilya Lemantieshiba Permana; Ike Junita Triwardhani (UNISBA Press, 2023)
Abstract. Today many Indonesian people, individually or in groups, use social media to carry out the communication process. One of them carried out by the Government of Bandung City. The Bandung City Government uses Instagram @humas_bandung as a bridge between the government and the community to convey messages. The message conveyed is not only information, but can also be in the form of ideas, instructions or feelings related to government policies, one of which is the content